3D Printing Technology as a Promising Tool to Design Nanomedicine-Based Solid Dosage Forms: Contemporary Research and Future Scope - Javed Ahmad; Anuj Garg; Gulam Mustafa; Abdul Aleem Mohammed; Mohammad Zaki Ahmad (MDPI AG, 2023)
3D printing technology in medicine is gaining great attention from researchers since the FDA approved the first 3D-printed tablet (Spritam®) on the market. This technique permits the fabrication of various types of dosage forms with different geometries and designs. Its feasibility in the design of different types of pharmaceutical dosage forms is very promising for making quick prototypes because it is flexible and does not require expensive equipment or molds. However, the development of multi-functional drug delivery systems, specifically as solid dosage forms loaded with nanopharmaceuticals, has received attention in recent years, although it is challenging for formulators to convert them into a successful solid dosage form. The combination of nanotechnology with the 3D printing technique in the field of medicine has provided a platform to overcome the challenges associated with the fabrication of nanomedicine-based solid dosage forms. Therefore, the major focus of the present manuscript is to review the recent research developments that involved the formulation design of nanomedicine-based solid dosage forms utilizing 3D printing technology. Utilization of 3D printing techniques in the field of nanopharmaceuticals achieved the successful transformation of liquid polymeric nanocapsules and liquid self-nanoemulsifying drug delivery systems (SNEDDS) to solid dosage forms such as tablets and suppositories easily with customized doses as per the needs of the individual patient (personalized medicine). Furthermore, the present review also highlights the utility of extrusion-based 3D printing techniques (Pressure-Assisted Microsyringe-PAM; Fused Deposition Modeling-FDM) to produce tablets and suppositories containing polymeric nanocapsule systems and SNEDDS for oral and rectal administration. The manuscript critically analyzes contemporary research related to the impact of various process parameters on the performance of 3D-printed solid dosage forms.